An overview of pregnancy diagnosis in small ruminants - KHARCHE, S D; KOUAMO, JUSTIN (The Indian Journal of Animal Sciences, 2015)
Accurate diagnosis of early pregnancy is a key factor for successful reproduction management in sheep and goat farm. Methods of pregnancy diagnosis depending on visualization of the conceptus or determination of its secretory products in the maternal blood or in the milk are the most accurate and specific methods for pregnancy. The use of determination of PAG concentration can help for pregnancy diagnosis and for new investigations on embryonic or fetal mortalities. The impetus is to develop reliable and practical on-farm/ranch tests for early pregnancy based on the presence of hormones or pregnancy-associated proteins. Non-return to estrus is still the easiest and cheapest method applicable at field and farm level. Real-time B-mode ultrasonic scanning of the uterus in goats and sheep appears to offer an accurate, rapid, safe and practical means for diagnosing pregnancy (from day 19), determination of fetal numbers, as well as for the identification of sex and prediction of gestational age and calving date in field conditions. The optimum time for using transabdominal or transrectal ultrasonography in small ruminants ranges from 19 to 100 days of gestation. Other techniques like laparoscopy, laparotomy, vaginal cytology and radiography although reliable are limited to the laboratory because of infrastructure and cost involvement. In many developing countries, farmers need to be educated on getting their animals checked for pregnancy at an early date as it was found that the earlier the pregnancy diagnosis performed the better the production and reproduction.